Superworm - Donaldson, Julia; Scheffler, Axel (New York, NY : Arthur A. Levine Books, an imprint of Scholastic Inc., 2014)
Superworm's bug friends attempt to free him from the clutches of Wizard Lizard who, having heard of Superworm's wondrous and heroic deeds, captures him and forces him to dig for treasure.
Kirkus Starred
Publisher's Weekly
Kirkus Starred, November 2013
Publisher's Weekly, November 2013
2.9
K-3.
Keywords: Heroes -- Juvenile fiction; Insects -- Juvenile fiction; Lizards -- Juvenile fiction; Wizards -- Juvenile fiction; Worms -- Juvenile fiction; Heroes -- Fiction; Insects -- Fiction; Lizards -- Fiction; Stories in rhyme; Wizards -- Fiction; Worms -- Fiction; Heroes and heroines -- Fiction; Insects -- Fiction; Lizards -- Fiction; Stories in rhyme; Wizards -- Fiction; Worms -- Fiction; Picture books for children